Palladium(II)-Catalyzed Oxidative ortho-Arylation of 2-Phenylpyridines - Feng, Jie; Lu, Guoping; Lv, Meifang; Cai, Chun (Synlett, 2013)
A palladium(II)-catalyzed oxidative ortho-arylation of 2-phenylpyridines via direct C–H activation with aryl boric acids is described. The reaction could be conducted under mild conditions in the presence of Pd(OAc)2/Cu(OTf)2/TBHP system, and a variety of the azacyclic compounds bearing a biaryl unit were obtained with moderate to good yields.
Keywords: palladium; C–H functionalization; ortho arylation; 2-phenylpyridines; arylboronic acid